ORGANOLEPTIC QUALITY OF BALITNAK KAMPUNG SUPERIOR CHICKEN MEAT WITH TURMERIC EXTRACT THROUGH DRINKING WATER - S., Wahyudi; Sriyani, N. L. P.; Puspani, E. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This research aims to determine the organoleptic quality of superior Balitnak chicken meat given turmeric juice through drinking water. The research design used was a Completely Randomized Design (CRD) which consisted of 4 treatments and 5 replications where each replication contained 2 superior village Balitnak chickens aged 10 days which had a 457 homogeneous weight. The four treatments were water without giving turmeric juice (Treatment P0), giving 1% turmeric juice (Treatment P1), giving 2% turmeric juice (Treatment P2), giving 3% turmeric juice (Treatment P3). The panelists used were 15 semi-trained panelists, each of whom received 9 samples using the hedonic and hedonic quality test methods which used a rating range of 1 to 5. The variables observed included meat color, meat flavor, meat texture, taste. meat, and overall acceptance. The results showed that the administration of 1%, 2% and 3% turmeric juice had a significant effect on meat color, meat flavor and overall acceptability of the meat, while there was no real effect on taste and texture. Then it can improve the organoleptic quality of Balitnak superior village chicken meat, especially in the variables of color, flavor and overall acceptability, while there is no improvement in the variables of taste and texture.